2016
DOI: 10.1371/journal.pone.0155034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2015 El Niño-Southern Oscillation on the Abundance and Foraging Habits of Guadalupe Fur Seals and California Sea Lions from the San Benito Archipelago, Mexico

Abstract: The abundance of California sea lions (Zalophus californianus) (CSLs) and Guadalupe fur seals (Arctocephalus philippii townsendi) (GFSs) from the San Benito Archipelago (SBA) was determined through nine monthly surveys in 2014–2015. Assessment of their foraging habits was examined based on the isotopic analysis of pups (maternal indicators) (SIAR/SIBER-R). Environmental variability between 2014 and 2015 was also analyzed, in terms of sea surface temperature (SST) and chlorophyll (Chl-a) concentration. Both ota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 38 publications
(73 reference statements)
1
50
1
Order By: Relevance
“…This change in foraging behavior may be a step to counter the negative effects of environment variability on prey availability and abundance (Kuhn and Costa , Elorriaga‐Verplancken et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…This change in foraging behavior may be a step to counter the negative effects of environment variability on prey availability and abundance (Kuhn and Costa , Elorriaga‐Verplancken et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Recent studies of GFS at San Benito Archipelago in Mexico during the 2015–2016 ENSO event showed declines in abundance and an increase of isotopic niche area, as a probable result of increase in foraging effort (Elorriaga‐Verplancken et al . ). Additionally, during this period, unprecedented records of emaciated GFS from the southern Gulf of California were recorded (Elorriaga‐Verplancken et al .…”
Section: Discussionmentioning
confidence: 97%
“…, Elorriaga‐Verplancken et al . ). Traditionally, in the Gulf of California, researchers have counted and categorized California sea lions ( Zalophus californianus ) in age and sex classes from boats, while circumnavigating rookeries and haul‐out sites (Le Boeuf et al .…”
Section: Statistic Summary Of the Generalized Additive Models K Are mentioning
confidence: 97%